UPACARA JIB BOK, MAI SONG, SANG CONG, DAN JIB GONG DALAM KHONGHUCU - Darno Darno (Analisa: Journal of Social Science and Religion, 2008)
Most of the death ceremony for Chinese descendant who are Khonghucufollower are similar particularly in Singkawang and generally in Indonesia.For instance, a Jib Bok ceremony, which is a ceremonial to enter thedeath people inti the box. Mai Song that is a ceremonial before departure to the cemetery held in the evening. Song Cong is a departure ritual,and Jib Gong is a buried service.